Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) ta có (a+b)2=a2+2ab+b2=a2+b2+2.6=a2+b2+12(1)
mà a+b=5 nên (a+b)2=25
từ(1) suy ra a2+b2=25-12=13
b) ta có (x+y)3=x3+y3+3xy(x+y)
suy ra x3+y3=(x+y)3-3xy(x+y)=125-90=35
Ta có: \(\frac{ab}{6+a-c}+\frac{bc}{6+b-a}+\frac{ca}{6+c-b}\)
\(=\frac{ab}{2a+b}+\frac{bc}{2b+c}+\frac{ca}{2c+a}\)
Áp dụng BĐT \(\frac{1}{a+b+c}\le\frac{1}{9}\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)\) với a,b>0
\(VT\le\frac{1}{9}\left(\frac{ab}{a}+\frac{ab}{a}+\frac{ab}{b}\right)+\frac{1}{9}\left(\frac{bc}{b}+\frac{bc}{b}+\frac{bc}{c}\right)+\frac{1}{9}\left(\frac{ca}{c}+\frac{ca}{c}+\frac{ca}{a}\right)=\frac{1}{3}\left(a+b+c\right)=2\)
Lời giải:
a)
\(a^2+b^2=a^2+b^2+2ab-2ab=(a+b)^2-2ab\)
\(=5^2-2.6=13\)
b) \(a^3+b^3=(a^2+b^2)(a+b)-a^2b-ab^2\)
\(=(a^2+b^2)(a+b)-ab(a+b)=13.5-6.5=35\)
c) \(a^4+b^4=(a^2+b^2)^2-2a^2b^2=13^2-2.6^2=97\)
d)
\(a^6+b^6=(a^3+b^3)^2-2a^3b^3=35^2-2.6^3=793\)
a=0
b=6
a = 0
b = 6
Hk tốt